2001
DOI: 10.1053/bbmt.2001.v7.pm11302551
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against infectious disease following hematopoietic stem cell transplantation

Abstract: Patients undergoing hematopoietic stem cell transplantation (HSCT) experience a prolonged period of dysfunctional immunity associated with an increased risk of bacterial and viral infections. Effective approaches toward vaccinating patients against common pathogens are being explored but are limited by poor levels of responsiveness. Relevant studies examining the nature of reconstitution of cellular and humoral immunity and its impact on vaccination strategies against infectious pathogens are reviewed. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 108 publications
1
34
0
Order By: Relevance
“…30 In fact, following HD-ChT, patients are more susceptible to opportunistic infections and to reactivation of persistent virus after transplantation. 7 When we analyzed the prevalence of infectious complications, surprisingly we found that patients with metastatic disease were apparently less vulnerable to VZV reactivation than patients with primary disease. Apparently, such findings would contradict the common observation that patients with advanced disease may have been heavily pretreated with cytotoxic chemotherapy and possibly they may be less immunocompetent than at earlier stage of disease.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…30 In fact, following HD-ChT, patients are more susceptible to opportunistic infections and to reactivation of persistent virus after transplantation. 7 When we analyzed the prevalence of infectious complications, surprisingly we found that patients with metastatic disease were apparently less vulnerable to VZV reactivation than patients with primary disease. Apparently, such findings would contradict the common observation that patients with advanced disease may have been heavily pretreated with cytotoxic chemotherapy and possibly they may be less immunocompetent than at earlier stage of disease.…”
Section: Discussionmentioning
confidence: 94%
“…5,6 Consistently, notwithstanding normal WBC values, in the early phase of recovery from HD-ChT, patients are susceptible to opportunistic infections such as Pneumocysti carinii, to endogenous reactivation of varicella zoster virus (VZV), and are not readily eligible for vaccination protocols. 7 Thus, specific approaches to enhance early recovery of CD28+ T cells after HD-ChT are necessary in order to abbreviate T cell immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Such impairment in antibody production has important consequences for revaccination in the HSCT recipient. 66 As delays in IgG2 and IgG4 production may impair T-cell-independent responses to polysaccharide antigens like Streptococcus pneumonia, a leading cause for bacterial infections in the context of GVHD. 67 Similarly, T-cell-dependent antibody production is delayed for at least 1 year after transplantation.…”
Section: Recovery Of Adaptive Immunitymentioning
confidence: 99%
“…The benefits of vaccination in HSCT recipients are clear (15), and this report should not alter current practice. Because of the expanding indications and growing numbers of HSCTs performed worldwide combined with improved survival, nephrologists need to be familiar with the renal complications of this life-saving procedure.…”
Section: Resultsmentioning
confidence: 96%